Role of Family and Community Health Center Employees in Controlling Dengue Fever in Puskesmas Antang Makassar - Loso Judijanti; Hamsir Ahmad; Inayah; Wahyuni Sahani; Ony Wibriyono Angkejaya (Postgraduate, University of Mataram, 2024)
The problem of dengue fever until now is still a problem which cannot be removed. The medicine of this desease is still not found to prevent transmission of dengue fever. The way to control dengue fever was by controlling the vector of transmission at the stage of the adult of egg phase, larvae, and pupae. It also included controlling mosquito adult phase. So that, in solving the problem, this research had purpose to find out and analyze the role of family and community health center employees in controlling dengue fever in Puskesmas Antang, Makassar. The method which was used in this research was observation by using case – control planning with descriptive analysis with quantitative and qualitative approach. It was done by giving the questionnaire to health center employees and public figures that involved that knew about dengue fever in this research. The result showed that 13.5% of informants had enough category in controlling this desease 86.5% of the informants were in less category. Having Lack of knowledge and action to prevent this disease could increase dengue fever to the health people. This research also can be used as the references for the next researchers.